Antibacterial property on Gram‐positive bacteria of polypyrrole‐coated fabrics. Issue 12 (11th November 2014) - Varesano, Alessio; Vineis, Claudia; Tonetti, Cinzia; Mazzuchetti, Giorgio; Bobba, Vittorio
ABSTRACT Antibacterial activity against Gram‐negative bacteria of polypyrrole‐coated fabrics has been demonstrated in the past. In this work, biocidal efficacy of polypyrrole has been evaluated against Gram‐positive bacteria on textiles with different polypyrrole loading. Excellent bacterial reduction (≥99%) was found on cotton fabrics containing more than ∼9 wt % of polypyrrole. Polypyrrole loading can be greatly reduced in presence of silver. Silver‐containing fabrics used in this work alone does not guarantee a complete biocidal effect, but the addition of just 2 wt % of polypyrrole showed a bacteria reduction of 99%. Moreover, stability to different washing procedures of the antibacterial activity was evaluated. Fabrics were characterized by scanning electron microscopy, energy dispersive X‐ray analysis, and infrared spectroscopy. Stability of the coating was assessed by abrasion tests. PPy showed excellent fastness to abrasion. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41670.